1997
DOI: 10.3168/jds.s0022-0302(97)76191-5
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Antibody Titers to Intramammary Immunization with Escherichia coli J5 Bacterin

Abstract: The effect of an immunization schedule on responses of antibody titers was tested following vaccination with an Escherichia coli J5 bacterin. Eighteen cows were equally distributed among three immunization schedules: 1) subcutaneous injection at 14 d prior to the end of lactation, intramammary immunization at 7 d after drying off, and subcutaneous injection at 30 d into the dry period; 2) subcutaneous injections at drying off, at 30 d into the dry period, and within 12 h after calving; and 3) unimmunized contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Currently, the J5 vaccines aim at inducing opsonic antibodies, and attempts to optimize the immune response are measured through increases in antibody titers (7,30,31). This is in keeping with the importance of phagocytosis by neutrophils as an essential defense of the mammary gland against E. coli (23).…”
Section: Figmentioning
confidence: 96%
“…Currently, the J5 vaccines aim at inducing opsonic antibodies, and attempts to optimize the immune response are measured through increases in antibody titers (7,30,31). This is in keeping with the importance of phagocytosis by neutrophils as an essential defense of the mammary gland against E. coli (23).…”
Section: Figmentioning
confidence: 96%
“…The route of immunization also appears to play a role in the antibody response. A vaccination schedule that included intramammary immunization between 2 subcutaneous immunizations resulted in higher serum antibody titers than the conventional vaccination schedule with 3 subcutaneous immunizations [20]. The enhancement of IgG and IgM titer responses in milk and serum by intramammary immunization has been explained by the possibility that cells stimulated locally in the mammary gland may travel to local lymphatic tissues, thereby increasing systemic antibody response [49].…”
Section: Effect Of Adjuvant and Administration Route On Antibody Respmentioning
confidence: 99%
“…Mucosal vaccines have shown to be effective both in the case of viral (i.e., oral polio vaccine, intranasal infectious bovine rhinotracheitis vaccine, oral rabies vaccine) and bacterial (i.e., oral cholera vaccine, oral E. coli vaccine, Staphylococcus aureus intramammary vaccine) pathogens (Levine et al, 2000;Pavot et al, 2012;Vilte et al, 2012;Gogoi-Tiwari et al, 2015). Hogan et al (1997) and Smith et al (1999) studied the effect of a systemic vaccination in combination with an intramammary E. coli J5 bacterin immunization schedule on responses of antibody titers. The results showed that intramammary immunization enhanced IgG titers in serum in the dry period and in lactation and in whey in early lactation compared with subcutaneous immunizations (Hogan et al, 1997;Smith et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Hogan et al (1997) and Smith et al (1999) studied the effect of a systemic vaccination in combination with an intramammary E. coli J5 bacterin immunization schedule on responses of antibody titers. The results showed that intramammary immunization enhanced IgG titers in serum in the dry period and in lactation and in whey in early lactation compared with subcutaneous immunizations (Hogan et al, 1997;Smith et al, 1999). However, the immunization schedule had minimal effect on systemic and local signs of clinical mastitis following challenge.…”
Section: Introductionmentioning
confidence: 99%